Accident Process and Core Thermal Response During a Station Blackout Initiated Study for Small Modular Reactor - Yin, Shasha; Tian, Yajing; Qiu, Suizheng; Tian, Ye; Fang, Huawei; Huang, Wei; Chen, Zhihui (Frontiers in Energy Research, 2018)
Interest in evaluation of reactor response and off-site consequences following beyond design basis accidents has significantly increased after Fukushima. Considering the inherent system safety of nuclear plants, experts begin to refocus on the development of small and medium nuclear reactors (SMRs). Based on proven and widely utilized traditional pressurized water reactor (PWR) technology, there are many kinds of small modular reactor design concepts, which are actively being developed in the USA, China, Japan, Russia, Korea, and other countries. And after Fukushima, interest in evaluation of reactor response and off-site consequences following beyond design basis accidents also has significantly increased. But due to the significant differences between the traditional distributed arrangement and integrated arrangement of SMRs, the variation trend of key parameters may be different during normal operation or accident process. So in this paper we simulated the small modular reactor severe accident by MELCOR. This papersummarizes the core thermal hydraulic response for a hypothetical severe accident caused by stationblackout at a small modular reactor using MELCOR. Analytical results for temperature distribution of the fuelpellets, the fuel cladding, flow rate of the coolant, andhydrogen mass changing over time arepresented.The analyses are focused on safety assessment of the reactor core for severe accidents and arepart of theoverall evaluation of safety features of the small modular reactor for residual risk posed by severeaccidents.